Contributing for myself, but free riding for my group? - Iida, Yoshio; Schwieren, Christiane (German economic review, 2019)
Abstract Many real-world decisions are made by individuals as representatives of groups. Most research, however, studies either individuals or groups as decision-makers. This paper explores whether there is a general difference between a decision made as an individual and as a representative of a group in the context of a public good game. We conducted a series of experiments to test this question and to understand mechanisms contributing to potential differences. We found that representatives contributed less than individuals when they could not communicate with their constituency. However, when they could discuss their strategy before playing, they contributed at least as much as individual decision-makers. Furthermore, when they could justify their decision after playing, they contributed even more than individual decision-makers. We discuss potential reasons for this and directions for future research.
Online veröffentlicht: 30.11.2019
Gesehen am 30.04.2020